(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This paper is devoted to examine the evolving role of smartphones in language acquisition, highlighting their potential to deliver interactive, personalized, and accessible learning. By integrating mobile applications, multimedia resources, and social networking platforms, smartphones extend traditional language learning approaches and facilitate dynamic and meaningful engagement with the target language. Through a review of current literature and emerging trends, this study explores the diverse opportunities presented by smartphones in connecting informal learning with linguistic ability. Recognizing both the benefits and challenges of technology integration in language education, this analysis contributes to a deeper understanding of how smartphones can be effectively utilized to cultivate proficient language speakers in an increasingly interconnected world.